A Correlational Study between Intrinsic Learning Motivation and Cyberslacking Behavior Among College Students - Putri Maharani; Ellina Rienovita; Lucia Ekawati Ikanubun (Jurnal Media dan Teknologi Pendidikan, 2025)
Cyberslacking behavior presents a significant challenge in the learning process, particularly among university students who have broad access to technology. This study aims to analyze the correlation between intrinsic learning motivation and student cyberslacking behavior. Intrinsic motivation in this study is based on Self-Determination Theory, encompassing the psychological needs for autonomy, competence, and relatedness. This research employed a quantitative approach with a correlational method. Data were collected using a closed-ended questionnaire with a Likert scale that had been tested for validity and reliability. A total of 167 students were selected as respondents through proportionate stratified random sampling. The Spearman rank correlation analysis revealed a significant negative correlation between intrinsic learning motivation and cyberslacking behavior (r = -0.200; p < 0.05). These findings indicate that higher intrinsic learning motivation is associated with a lower tendency to engage in cyberslacking during learning activities. The results highlight the importance of fostering intrinsic motivation as a preventive strategy against cyberslacking. The implication of this study encourages educators and instructional designers to develop learning experiences that support students’ basic psychological needs optimally.